IMPLEMENTATION OF EMPLOYER BRAND EQUITY AS AN EFFORT TO REDUCE INTENTION TO LEAVE AT PT GEMILANG PLASTAMA CEMERLANG - Putri, Elvani Anisa; Dwianto, Agung Surya (ANALISIS, 2023)
This study aims to analyse the effect of employer brand equity of PT Gemilang Plastama Cemerlang, namely social value, interest value, development value, application value, economic value. As well as the effect of employer brand equity on intention to leave. The research method used is associative quantitative research method, where the data collection method is done by distributing questionnaires. The population in this study were all Gen Z, totalling 100 people. Sample withdrawal is done by saturated sampling method. Data processing using SPSS version 26 software, with descriptive analysis and multiple linear regression analysis hypothesis testing. The results showed that (1) partially social value has a positive and significant influence on interest value (2) partially development value has a positive and significant influence on application value. (3) simultaneously there is a positive and significant influence between economic value variables and intention to leave. These findings can be input for employers in making decisions as a strategy to increase comfort for employees, especially in shaping employer brand equity to employees.